What is the domain for weight computation: the syllable or the interval? - Aron Hirsch (Amherst demo, 2014)
The distribution of lexical stress is sensitive to the weight of rhythmic units such that heavier units more strongly attract stress. This paper addresses the question: what is the rhythmic unit relevant for weight computation? The traditional approach links weight to the syllable: weight is computed over the syllable rime (review in Blevins 1995), possibly with limited onset-sensitivity (Kelly 2004, Gordon 2005, Ryan 2013). I present experimental data which challenge this view, and support a recently proposed non-syllable-based alternative according to which weight is computed over the total vowel-to-vowel interval (Steriade 2012). Using a nonce word production paradigm, I test how likely participants are to stress the initial vs. final vowel in bi-vocalic sequences, manipulating the consonantal interlude separating the two vowels between a single C (e.g. aka) and CC cluster (akra). Initial stress is more likely with CC than C – medial consonants contribute weight to pull stress to the initial vowel, CC contributing more weight than C. This is incompatible with syllable constituency which parses C/CC in the onset of the final syllable (a.ka, a.kra), and supportive of interval constituency which parses C/CC in the initial interval (ak*a, akr*a).
Keywords: syllables; intervals; weight; Stress; Experimental